FASAKH DAN KHULU’ SEBAGAI SOLUSI HUKUM ATAS PERNIKAHAN PAKSA: ANALISIS NORMATIF-USHULI DAN RELEVANSINYA DALAM PRAKTIK PERADILAN AGAMA - Muhammad Verdy Ardiansyah; Dr. Muhsan Syarifuddin, Lc., M.H.I. (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines the relevance of fasakh and khulu' as legal solutions to forced marriage through normative-ushuli analysis and its relevance in the practice of religious justice in Indonesia. The method used is qualitative through literature study in normative legal research with legislative, conceptual, case, and uṣūl al-fiqh approaches. The analysis is carried out through the stages of problem description, legal classification, 'illat verification, and legal determination. Data sources include the Qur'an, hadith, ijma', laws and regulations, classical and contemporary fiqh literature, works of salaf scholars, academic books, journal articles, legal dictionaries, encyclopedias, and credible online sources. The results of the study show that forced marriage is a defective contract because the element of willingness is not fulfilled, so it is included in the category of the fāsid contract. Fasakh and khulu' proved to be relevant as instruments of its solution. Fasakh can be filed to cancel the contract due to coercion, while khulu' gives the wife the right to apply for a marriage termination through the court by giving a reward ('iwadh) without waiting for the husband's talaq. Both have a strong shari'i basis through the Qur'an, hadith, ijma' ulama, and fiqh rules such as lā ḍarar wa lā ḍirār and ad-dhararu yuzāl, and are strengthened by the positive legal provisions that apply in Indonesia. Thus, the novelty of this research lies in the integration of the analysis of uṣūl al-fiqh and Indonesian positive law in the settlement of forced marriage.